Clementi and the Woman at the Piano: Virtuosity and the Marketing of Music in Eighteenth-century London - Helyard, Erin (Liverpool Oxford Liverpool University Press Voltaire Foundation, 2022)
"This book takes as its historical point of departure the radical appearance in 1779 of technically difficult keyboard music in a set of six sonatas (Op. 2) by Muzio Clementi. The difficult passages contained in this opus are unique among keyboard works published for a market that was understood at the time to consist almost entirely of female amateur keyboardists. Previously actively discouraged from practicing or improving their skills due to the restrictive ideologies in place, female pianists are increasingly offered a new kind of musical expression by Clementi's music. 'Clementi and the woman at the piano: virtuosity and the marketing of music in eighteenth-century London' maps the social, musical, and gendered implications of technically difficult music, and helps to underline important changes in Enlightenment culture and keyboard practice. Clementi's activities initiated the now familiar and modern concepts of repetitive musical practice, the work-concept, virtuosity itself, and the distinction between amateur and professional. Additionally, Clementi promotes a radical new mode of expression for female pianists that is at first highly controversial but slowly gains acceptance due to a widespread promotion of his music, instruments, and methods. Clementi's career is in many respects a perfect case study for the tensions between Enlightenment thinking and new Romantic ideologies."--Page 4 of printed paper wrapper.
Clementi and the Enlightenment -- Mozart's insult and the irritations of virtuosity -- Keyboard performance and gender in Eighteenth-century London -- Clementi's "Black Joke" -- Male 'theoria' and female 'praxis' -- Clementi in the marketplace and the Conservatoire -- Conclusion: Clementi's Coin -- Appendix: Ideological differences regarding keyboard practicing/music education in thirty-six conduct books and treatises, 1741-1829.
Includes bibliographical references (pages 281-308) and index.
Includes quotations in German or French, some with English translation.
Keywords: Clementi, Muzio -- 1752-1832; 18th Century (1701-1800); Keyboard music; Music history; Sociology; Gender; Female; Virtuosity; Performance; London (United Kingdom)